The Impact of Counseling on Compliance with Iron Tablet Consumption Among Pregnant Women: A Pre-Experimental Study - Astuti, Wuri Widi; Asiyah, Siti; Putri, Erlina Rahma (Journal of Applied Nursing and Health, 2025)
Background: Prevention of anemia in pregnant women by government programs given 90 iron supplement tablets during pregnancy. Giving iron will increase levels of hemoglobin. Compliance with iron tablet consumption influences the incidence of anemia in pregnant women. The research aimed to determine the effect of counseling on compliance with consuming iron tablets at the Gampeng Community Health Center, Kediri Regency.  Methods: The research design used was a pre-experiment, a one-group pretest, and a post-test with a population of 52 pregnant women and a sample of 46 pregnant women obtained by the simple random sampling technique. The inclusion criteria were pregnant women who were willing to be respondents, pregnant women in the first and third trimesters, and pregnant women without complications such as emesis or hyperemesis. The pre-test was carried out before the intervention, and the intervention was given once for 60 minutes. A post-test was then carried out after 7 days to see compliance with the consumption of iron tablets. Results: The Mc Nemar test was used for statistical analysis (α =0.05). The study results were obtained before the intervention; Most pregnant women (56.6%) were compliant with consuming iron tablets, and after the intervention, Almost all pregnant women (93.5%) were compliant with consuming iron tablets. Statistical results obtained a p-value of 0.000 (α = 0.05), which means that counseling affected compliance with iron tablets at the Gampeng Community Health Center, Kediri Regency. Conclusion: The results indicated the impact of counseling on pregnant women consuming iron tablets. Improving the knowledge of pregnant women can enhance iron adherence tablet consumption. ANC visits should be optimized to provide health information (especially about the importance of taking iron tablets).